RANCANG BANGUN APLIKASI E-COMMERCE PRODUKSI SENI KREATIF PADA MOPIN: ART PROJECT DI SURAKARTA - Alvin Dharmawan (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2021)
MOPIN: Art Project is a workshop in the arts and provides various artistic products. The problem faced by MOPIN: Art Project is a sales system that is still manual, with consumers having to come directly to the workshop if they want to buy products. The research aims to build an e-commerce application for creative crafts on MOPIN: Art Project so it produces an online store that can be used properly. The method used a waterfall approach. The waterfall method is used to develop the system through sequential stages, namely analysis, design, coding, and testing. System analysis used PIECES method and system design used (UML) Unified Modelling Lenguage. This research produces a website-based e-commerce application with Home, Products, Contacts, Shopping Cart, Admin Pages, and Member Pages menus. The results of webqual testing of 4 factors, namely Usability Quality, Information Quality, Service Interaction, and Overall, shows the results from the total quality of the website are 64.7%, so it can be concluded that the quality of the website is quite good